Manifestation of migraine in adolescents: Does it change in puberty?. (May 2020) - Böttcher, B.; Kyprianou, A.; Lechner, C.; Kößler, M.; Heinz-Erian, E.; Neururer, S.; Abdel Azim, S.; Wildt, L.; Toth, B.; Baumann, M.; Rauchenzauner, M.; Rostásy, K.
Abstract: Purpose: To analyze the association between pubertal stage, menstrual cycle and migraine attacks in girls with migraine. In addition, headache frequency, accompanying symptoms, duration and onset in relation to the specific phase of the cycle were investigated. Methods: Girls between 7 and 18 years old, diagnosed with headaches that met "International Classification of Headache Disorders II" diagnostic criteria for migraine without aura, kept a daily headache and menstrual cycle diary over 8 weeks. Ovulatory cycles were identified by weekly progesterone saliva tests. Results: 47 girls participated in the study and were divided into three groups according to Tanner stage and onset of regular menstruation: pre- (n = 16), peri- (n = 19) and post-pubertal (n = 12). A significant difference in migraine frequency was found between pre- and post-pubertal girls (p = 0.005). No significant differences with regard to headache characteristics were detected. Interestingly, a higher frequency of attacks in follicular phase occurred compared to luteal phase in peri- and post-pubertal girls (p = 0.030). Conclusion: During puberty, migraine patterns in girls change to a typical adult pattern of migraine in a stepwise manner not clearly related to menarche. The first sign of this transition phase could be the higher frequency of migraine attacks in post-pubertal girls. Highlights: Post-pubertal girls suffer from a higher frequency of migraine attacks than prepubertal girls. Headache characteristics did not differ comparing pre- and post-pubertal girls. More attacks seem to occur during follicular phase. The change to an adult migraine pattern is a stepwise development. An increasing migraine frequency might be the first step towards an adult pattern.